Combined effect of health behaviours and risk of first ever stroke in 20 040 men and women over 11 years’ follow-up in Norfolk cohort of European Prospective Investigation of Cancer (EPIC Norfolk): prospective population study - Myint, Phyo K (BMJ Publishing Group Ltd., 2009)
Objective To quantify the potential combined impact of four health behaviours on incidence of stroke in men and women living in the general community. Design Population based prospective study (EPIC-Norfolk). Setting Norfolk, United Kingdom. Participants 20 040 men and women aged 40-79 with no known stroke or myocardial infarction at baseline survey in 1993-7, living in the general community, and followed up to 2007. Main outcome measure Participants scored one point for each health behaviour: current non-smoking, physically not inactive, moderate alcohol intake (1-14 units a week), and plasma concentration of vitamin C ≥50 µmol/l, indicating fruit and vegetable intake of at least five servings a day, for a total score ranging from 0 to 4. Results There were 599 incident strokes over 229 993 person years of follow-up; the average follow-up was 11.5 years. After adjustment for age, sex, body mass index (BMI), systolic blood pressure, cholesterol concentration, history of diabetes and aspirin use, and social class, compared with people with the four health behaviours the relative risks for stroke for men and women were 1.15 (95% confidence interval 0.89 to 1.49) for three health behaviours, 1.58 (1.22 to 2.05) for two, 2.18 (1.63 to 2.92) for one, and 2.31 (1.33 to 4.02) for none (P<0.001 for trend). The relations were consistent in subgroups stratified by sex, age, body mass index, and social class, and after exclusion of deaths within two years. Conclusion Four health behaviours combined predict more than a twofold difference in incidence of stroke in men and women.